Pengaruh Ukuran Perusahaan, Non Performing Loan, Loan Deposit Ratio, Profitabilitas terhadap Nilai Perusahaan - Yogi Rakha Pranolo; Mahroji (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to analyse the impact of standard banking financial reporting on business value from 2019 to 2022 in relation to profitability, non-performing loans, firm size, and the loan-deposit ratio. Using purposive selection criteria, ten firms were chosen for the research, and forty data samples were examined. Secondary data includes financial information sourced from www.ojk.go.id. Various SPSS research techniques, such as logistic regression analysis, as well as conventional assumption tests and multiple regression analysis models, were used to examine the data. These variables are shown by the study findings. A company's worth is negatively affected by its loan-to-savings ratio and positively affected by its size. To be more precise, NPL and ROA do not impact the value of a firm. Having knowledge about the company's accomplishments and present state will increase faith in the company's principles. Consequently, investors are eager to put their money into this company.